2018
DOI: 10.3389/fonc.2018.00486
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Vascular Endothelial Growth Factor for Nasopharyngeal Cancer Prognosis

Abstract: Background: Vascular endothelial growth factor (VEGF) has been reported to serve as a promising prognostic marker in several cancers. This meta-analysis aims to assess the prognostic significance of VEGF in nasopharyngeal cancer (NPC).Methods: We conducted a systematic literature search of PubMed, Embase, and the Cochrane Library for observational studies published until June, 2018 to identify observational studies on the prognostic effect of tissue VEGF expression or serum VEGF level on the survival of NPC. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Therefore, the association between VEGF and AMPK α1 levels in NSCLC were investigated. Consistent with previous reports (9,10), it was concluded that VEGF was more highly expressed in NSCLC tissues compared with adjacent non-tumor lung tissues (Fig. 2A), and higher levels of VEGF were associated with a poorer prognosis (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, the association between VEGF and AMPK α1 levels in NSCLC were investigated. Consistent with previous reports (9,10), it was concluded that VEGF was more highly expressed in NSCLC tissues compared with adjacent non-tumor lung tissues (Fig. 2A), and higher levels of VEGF were associated with a poorer prognosis (Fig.…”
Section: Resultssupporting
confidence: 91%
“…VEGF is a key factor of tumor neoangiogenesis [14]. It has been shown that overexpression of VEGF is an overall indicator of poor survival in various tumor entities emphasizing its clinical importance [40][41][42]. Therefore, it may be beneficial, when imaging can correctly predict VEGF expression of tumors enabling a non-invasive and serial approach compared to bioptic samples.…”
Section: Discussionmentioning
confidence: 99%
“…Both tumor cells and surrounding stromal cells secrete VEGF to stimulate the proliferation and survival of endothelial cells and form new blood vessels [ 7 ]. VEGF is expressed in most human cancers, and elevated VEGF expression levels are often related to a less favorable prognosis in cancer patients [ 6 , 8 ]. Bevacizumab is the first US Food & Drug Administration (FDA)-approved recombinant humanized anti-VEGF monoclonal antibody for the treatment of non-small cell lung cancer (NSCLC), metastatic breast cancer, metastatic colorectal cancer, and other solid tumors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%